The Singapore method for teaching and learning maths: a proposal for the 2nd year students. - Rodríguez-Martínez, Marina (My University, 2022)
This final degree work presents a didactic unit focus on the learning of the mathematics based in the Singapore method for the students of 2nd year. It is common knowledge that some students present problems while they are learning this subject with a traditional method where they just use a formula without understanding what they are really doing. This is why this method powered by Yeap Ban Har and based in different methodologies proposed by authors like Piaget, Bruner, Dienes and Skemp. The main objective of this method is to provide the students a new way to achieve new knowledges while they reinforce what they already have learnt. An analysis of the method will be done to understand the methodology, implications and the problem solving in order to plan a didactic unit based in the learning of the multiplications for the students of 2nd year. The purpose of this didactic unit is to improve the learning outcomes of the mathematics while developing the proposed methodology.
Keywords: Singapore method; problem solving; mathematics; methodology; 2nd year; Grado en Maestro en Educación Primaria